2022
DOI: 10.1101/2022.07.22.501138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multispecies biofilm architecture determines bacterial exposure to phages

Abstract: Numerous ecological interactions among microbes - for example, competition for space and resources, or interaction among phages and their bacterial hosts - are likely to occur simultaneously in multispecies biofilm communities. While biofilms formed by just a single species occur, multispecies biofilms are thought to be more typical of microbial communities in the natural environment. Previous work has shown that multispecies biofilms can increase, decrease, or have no measurable impact on phage exposure of a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 91 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…In this case, almost all cells of both species were killed off by the predators (SI Figure S3C,D). In a parallel study illustrating the generality of these results, we show that E. coli embedded along the bottom layers of expanding V. cholerae biofilm clusters are also protected from exposure to the obligate lytic phage T7 and temperate phage l in a manner dependent on the high packing structure of V. cholerae biofilms (78).…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…In this case, almost all cells of both species were killed off by the predators (SI Figure S3C,D). In a parallel study illustrating the generality of these results, we show that E. coli embedded along the bottom layers of expanding V. cholerae biofilm clusters are also protected from exposure to the obligate lytic phage T7 and temperate phage l in a manner dependent on the high packing structure of V. cholerae biofilms (78).…”
Section: Resultsmentioning
confidence: 63%
“…In this case, almost all cells of both species were killed off by the predators (SI Figure S3C,D). In a parallel study, we show that all of these results are replicated if virulent lytic or temperate phages targeting E. coli are introduced to biofilms of E. coli and V. cholerae grown in co-culture (Winans et al, 2022, bioRxiv) 77 .…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…The collective protection from phage attack in a colony is empowered further when the bacteria produce extracellular structures that constitute a large part of the biofilm [46]. For example, the collective protection by expression of curli polymer that can trap T7 phage enables matured enough E. coli biofilm to keep growing under phage attack [47,48]; more complex collective protection has been reported recently in a multispecies biofilm [49]. A simulation study confirmed that the mobility of phage is the key when attacking a biofilm [50].…”
Section: Eliminating the Winner: Ongoing Reshuffling Of Bacterial Fit...mentioning
confidence: 76%